Out-of-hospital resuscitation in East Sussex: 1981 to 1989. Issue 6 (December 1993) - Lewis, S J; Holmberg, S; Quinn, E; Baker, K; Grainger, R; Vincent, R; Chamberlain, D A
Abstract : OBJECTIVE--To assess the impact of extended training in advanced life support on the outcome of resuscitation. DESIGN--Analysis of the successful resuscitations from 1981 to 1989. SETTING--Brighton and East Sussex. RESULTS--248 patients were resuscitated from cardiac or respiratory arrest in the community and subsequently survived to leave hospital. Their mean age was 64 years and one year survival was 77%. In most cases the cause of collapse was cardiac but 38 (15%) suffered a respiratory arrest. In 140 of the successful resuscitations (56%) collapse occurred before the arrival of the ambulance. Basic life support, with ventilation and chest compression where necessary, was sufficient to revive 35 (14%) of the patients. Defibrillation was also required in 107 patients (43%), and in a further 106 patients (43%) who had prolonged cardiorespiratory arrest requiring endotracheal intubation and the use of several drugs. Review of ambulance forms and case notes showed that in 87 cases (35%) the abilities of the paramedical ambulance staff in advanced resuscitation techniques contributed decisively to the success of resuscitation. These skills are illustrated by eight case reports. CONCLUSIONS--Extended training for ambulance staff increases the likelihood of successful resuscitation from out-of-hospital cardiopulmonary arrest. Though instruction in defibrillation must have the highest priority, full paramedical training can bring appreciable additional benefits.